2017
DOI: 10.14218/jcth.2017.00009
|View full text |Cite
|
Sign up to set email alerts
|

Current Modalities of Fibrosis Assessment in Non-alcoholic Fatty Liver Disease

Abstract: Non-alcoholic fatty liver disease (NAFLD) is a burgeoning global health concern. In the subset of NAFLD patients with non-alcoholic steatohepatitis (NASH), the presence of significant fibrosis at index assessment is associated with poor prognosis and increased mortality. Hence, there is a growing need to accurately assess and stage fibrosis. Liver biopsy, the current gold standard, has limitations with sampling error and is invasive, with associated inherent risk. This has led to a host of non-invasive means o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
74
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(78 citation statements)
references
References 112 publications
(141 reference statements)
2
74
0
2
Order By: Relevance
“…In this regard, it should be noted that the diagnostic performances of compound surrogates may be influenced by potential confounders (e.g., patient age, prevalence of different fibrosis stages, and different NAFLD disease spectrum). [12][13][14][15][16][17][18][19] These limitations notwithstanding, our results indicate that the main clinical utility of FIB-4 and NFS in patients with NAFLD lies in their ability to exclude, rather than identify, advanced fibrosis. Specifically, the routine application of FIB-4, a simple compound surrogate based on four parameters, is expected to reduce the number of liver biopsy by nearly 70%.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, it should be noted that the diagnostic performances of compound surrogates may be influenced by potential confounders (e.g., patient age, prevalence of different fibrosis stages, and different NAFLD disease spectrum). [12][13][14][15][16][17][18][19] These limitations notwithstanding, our results indicate that the main clinical utility of FIB-4 and NFS in patients with NAFLD lies in their ability to exclude, rather than identify, advanced fibrosis. Specifically, the routine application of FIB-4, a simple compound surrogate based on four parameters, is expected to reduce the number of liver biopsy by nearly 70%.…”
Section: Discussionmentioning
confidence: 99%
“…methods [2][3][4][5][6][7][8][9][10][11][12], including imaging modalities [13][14][15][16][17], biomarkers [18][19][20][21][22][23][24][25][26], and artificial intelligence algorithms [27][28][29][30][31][32].…”
mentioning
confidence: 99%
“…3,4 In the United States, the number of individuals with NASH is estimated to be more than 11 million, and our ability to delineate which patients with NAFLD have NASH remains poor at present. The long-standing use of liver enzymes to differentiate these different entities has been debunked and proved inadequate, [4][5][6][7] and despite extensive work in the research realm, no other straightforward serological tests or panels have shown results convincing enough to usurp the previous gold standard. 6,7 The outdated dogma of liver biopsy being the gold standard for identifying those at risk among these millions of patients would mean extrapolating to this population the known severe complication rate of 1.1% 8 and mortality rate of 0.3%.…”
mentioning
confidence: 99%
“…The long-standing use of liver enzymes to differentiate these different entities has been debunked and proved inadequate, [4][5][6][7] and despite extensive work in the research realm, no other straightforward serological tests or panels have shown results convincing enough to usurp the previous gold standard. 6,7 The outdated dogma of liver biopsy being the gold standard for identifying those at risk among these millions of patients would mean extrapolating to this population the known severe complication rate of 1.1% 8 and mortality rate of 0.3%. 9 If we are to appropriately identify the NAFLD population most at risk for progression to cirrhosis by means of biopsy, it corresponds to daunting figures of morbidity and death.…”
mentioning
confidence: 99%